Small is the new big: An overview of newer supraglottic airways for children - Rakhee Goyal (Wolters Kluwer Medknow Publications, 2015)
Almost all supraglottic airways (SGAs) are now available in pediatric sizes. The availability of these smaller sizes, especially in the last five years has brought a marked change in the whole approach to airway management in children. SGAs are now used for laparoscopic surgeries, head and neck surgeries, remote anesthesia; and for ventilation during resuscitation. A large number of reports have described the use of SGAs in difficult airway situations, either as a primary or a rescue airway. Despite this expanded usage, there remains little evidence to support its usage in prolonged surgeries and in the intensive care unit. This article presents an overview of the current options available, suitability of one over the other and reviews the published data relating to each device. In this review, the author also addresses some of the general concerns regarding the use of SGAs and explores newer roles of their use in children.